MASYARAKAT LOKAL DAN PROGRAM REKLAMASI LAHAN BEKAS TAMBANG DI DESA BANJAR SARI KECAMATAN ANGSANA - Muhammad Iswahyudi; Wahyu Wahyu; Machfudz Shiddiq; Muhammad Ermayn Erhaka (Universitas Lambung Mangkurat, 2013)
Coal mining has taken place in the framework as a support system for life and growth capital. The presence of coal mining could not be avoided because its presence is needed by humans. However, management of natural resources needs to be understood according to the dynamics and needs. Mining is identical with the land degradation in its management must meet the rule of good mining practices. One integral part of the rules good mining practices is reclaimation. Reclamation is an ideal covering at least three aspects, namely the government: the mining company, and society. Aspect is seen in this study is the role of communities in mined land reclamation. Society should not be positioned as an object affected only but should be the subject of a core part in the formulation of environmental management, in this case is reclamation. The purpose of this study to: (1) know the description of local community participation in planning the reclamation of mined land and (2) identify factors that support and hinder the participation of local communities in the village of Banjar Sari Angsana District. Mining in the village of Banjar Sari has been ongoing since 2006. Mining activities take place in the midst of human settlements and the impact of environmental change are felt by the community. Real scene and its impact on land mines can be seen easily in the midst of residential communities. The results showed that no picture of Participation of local communities in planning the mined land reclamation. The situation is further highly influential in the future such as community participation in the implementation and evaluation of reclamation. There are several factors that affect local people's involvement in this reclamation. Factors that can support community participation has been the availability regulation is to ensure public participation, the availability of communication institutional system of society, and society has to have sufficient knowledge about the relationship of mining and environmental quality. The factors that inhibit the function of public participation is weak and the government's role in empowering the community, the good faith of the mining company, is less strong on the rights and obligations of information society in environmental management.